Auditory Discrimination Between Function Words in Children and Adults: A Mismatch Negativity Study - Strotseva-Feinschmidt, Anna; Cunitz, Katrin; Friederici, Angela D.; Gunter, Thomas C. (Frontiers in Psychology, 2015)
Previous behavioral studies showed that it is not until around the age of seven that German children reliably use case markers for the interpretation of complex sentences. Some explanations of this late development suggested that children might have difficulties in perceptual differentiation between function words that carry case information. We tested this hypothesis by using the neurophysiological index of pre-attentive discrimination, the mismatch negativity (MMN). Our data showed that children at the age of three years are able to automatically discriminate between the two determiner forms der and den when presented out of sentential context. The determiner form der elicited a more mature MMN response in children than the form den. In adults, the MMN pattern also differed with der showing an earlier peak than den. These findings indicate that der is easier to process than den, which in turn is related to the occurrence frequency of the determiner forms in language.